Analisis Faktor Host terhadap Kecacatan Kusta Tingkat II Di Kabupaten Nagan Raya Provinsi Aceh - T.M. Rafsanjani; Djoko Trihadi Lukmono; Henry Setyawan; Anies Anies; Sakundarno Adi (Jurnal Vokasi Kesehatan, 2018)
Abstract: An Analysis Of Host Factors Toward The Level Ii Leprosy Disability In Nagan Raya Regency, Aceh Province. The leprosy disabilities level II is often experiencing the limitations in function among societies. In Nagan Raya Regency, there are 41% endemic areas with the number of level II disability for 5%. This research aims to prove some host and environment factors that become the risk factors for disability for level II leprosy. Case-control methods and interview methods were chosen as the design of control case in this research. 84 respondents were involved in conducting case-control design, and 42 cases of leprosy disabilities level II and 42 control of leprosy without disabilities, selected with consecutive sampling by considering the criteria of inclusion and exclusion. The results of this research were analyzed with bivariate by using chi-square test and the multivariate data were analyzed by using logistic regression test. Four variables that had the risk towards leprosy level II disability were at the age of the diagnosis time > 15 p=0,039 and OR=8,4 (CI 95%; 1,1-63,3), level of education p=0,038 and OR=3.4 (CI 95%; 1,1-10,9), too late to do early diagnosed p=0,011 and OR=5,4 (CI 95%; 1,5-19,6), types of leprosy MB p=0,015 and OR=3,9, (CI 95%; 1,3-12,1). Some host factors were proven to have risk towards leprosy disability of level II are the age at the time of diagnosis > 15 years, too late to do early diagnosis and leprosy types MB with the probability of 99.96 %. It is expected for the team of Public Health Office to conduct prevention in a productive age population, early case detection to prevent disability, and socialized the patient about the dangers of leprosy.Abstrak: Analisis Faktor Host Terhadap Kecacatan Kusta Tingkat II Di Kabupaten Nagan Raya Provinsi Aceh. Kecacatan kusta tingkat II mengalami keterbatasan pada fungsinya dalam masyarakat. Kabupaten Nagan Raya terdapat 41% daerah endemis, dengan kecacatan tingkat II sebanyak 5%. Penelitian ini bertujuan untuk membuktikan beberapa faktor host merupakan faktor risiko kecacatan tingkat II. Penelitian ini menggunakan desain kasus kontrol terhadap 84 responden,Â  dari 42 kasus (cacat kusta tingkat II) dan 42 kontrol (kusta tanpa cacat),Â  yang dipilih secara consecutive sampling dengan memperhatikan kriteria inklusi dan eksklusi. Pengumpulan data dilakukan dengan metode wawancara. Analisis data secara bivariat dengan uji Chi-Square dan multivariat dengan uji regresi logistik. Empat variabel merupakan faktor risiko terhadap kecacatan kusta tingkat II, yaitu umur saat diagnosis > 15 tahun p=0,039, OR=8,4 (CI 95%; 1,1-63,3), tingkat pendidikan p= 0,038, OR=3,4 (CI 95%; 1.1-10.9) diagnosis dini lambat p=0,011, OR=5,4 (CI 95%; 1,5-19,6), tipe kusta MB p=0,015, OR=3,9, (CI 95%; 1,3-12,1). Beberapa faktor host terbukti berisiko terhadap kecacatan kusta tingkat II adalah umur saat diagnosis > 15 tahun, tingkat pendidikan, diagnosis dini lambat, dan tipe kusta MB dengan probabilitas sebesar 99,96%. Diharapkan kepada dinas kesehatan melakukan pencegahan kelompok usia produktif, penemuan kasus secara dini untuk mencegah kecacatan dan memberikan pemahaman terhadap penderita tentang bahaya kusta